Nivel de conocimiento y su relación con la actitud ambiental en pobladores del asentamiento humano Masusa en el distrito de Punchana, Maynas – 2021 - Silva del Aguila, Dustin Javier (2025)
The general objective of this research work was to determine the relationship between the level of knowledge on environmental issues and the attitude towards environmental conservation in heads of family of the Masusa human settlement. 2021 The research was quantitative, simple relational and non experimental in design. The target population of the study was considered to be the total number of heads of family in said human settlement, and the sample was equal to 101 heads of family. Inclusion and exclusion criteria were included, using the survey technique and as an instrument two questionnaires of ten items each, evaluated with validity tests using the Aiken Validity index and reliability with the Crombach's Alpha test with Pearson's r statistic. The data were analyzed and processed through the SPSS v27 statistical package. The results indicate that there is no high level of knowledge on environmental issues, with regular and low being the predominant ones. Likewise, there are no differences in the level of knowledge on environmental issues according to gender and level of education, with regular and low knowledge predominating in each case. There is no favorable or very favorable predisposition or attitude towards environmental conservation, since the general, cognitive, and affective attitude was neutral and reactive was unfavorable. There is a significant indirect association but of low intensity between the level of knowledge on environmental issues and the general attitude towards environmental conservation in the heads of families of the AAHH Masusa, at a level of 0.05 probability. It is necessary to strengthen environmental knowledge and attitudes in order to reverse the meaning of this association in the population studied.